Sustainability through Website Development: The Case of Public Libraries in Malaysia - Bakar, Ahmad Bakeri Abu; Jaafar, Putri Nur Liyana (Qualitative and Quantitative Methods in Libraries; Vol 2 No 1 (2013): March 2013 Issue, 2017)
With the introduction of the World Wide Web and graphical browsers in the 1990s the Internet has become widely accessible and many people have grabbed the idea of using it for their multifarious purposes and agenda The library website is the most important window and the gateway for interactivity with the publics.  So much so that higher quality websites tend to exhibit high traffic pattern and  are capable of attracting more links and thereby rendered those websites as highly visible.    The question of visibility and accessibility is therefore important for any type of websites and should be addressed painstakingly with the notion that sustainable development of the website may assist the library in reaching its goals. Through the development of quality websites libraries in Western countries are able to sustain their growth through generating income through charges, particularly for access to unique materials, making it attractive to sponsors or  making it possible for third parties to deliver their own services based on website contents. It is the purpose of this paper to study on the question of visibility and accessibility of the websites of selected public libraries in Malaysia through the use of two major software, Alexa and EvaAcess.